2006
DOI: 10.1002/uog.2729
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between color Doppler cineloop‐ and conventional spectral Doppler‐derived maximum velocity and flow in the umbilical vein

Abstract: Objective

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 23 publications
(82 reference statements)
1
15
0
Order By: Relevance
“…It clearly shows that there is a trend to find higher values of flow when mean velocities are estimated from the IWMV compared with from the mean and maximal velocity20, 23, 25, 26, 37. Accordingly, Gerada et al 29, summarizing the findings of 20 published studies on umbilical venous flow, also reported that studies in which mean velocities were estimated from the IWMV show higher blood flow values at 30 weeks. However, estimating the mean velocity from Vmax cannot be considered error‐free either.…”
Section: Accuracymentioning
confidence: 91%
See 2 more Smart Citations
“…It clearly shows that there is a trend to find higher values of flow when mean velocities are estimated from the IWMV compared with from the mean and maximal velocity20, 23, 25, 26, 37. Accordingly, Gerada et al 29, summarizing the findings of 20 published studies on umbilical venous flow, also reported that studies in which mean velocities were estimated from the IWMV show higher blood flow values at 30 weeks. However, estimating the mean velocity from Vmax cannot be considered error‐free either.…”
Section: Accuracymentioning
confidence: 91%
“…The umbilical vein is the longest venous vessel in the human fetus and it has been demonstrated in vivo that, at its free‐floating portion, its diameter decreases progressively from the fetus to the placenta13. Both intra‐abdominal1, 4, 10, 14–24 and free‐floating21, 25–29 portions of the umbilical vein have been used to estimate vessel area. When a free‐floating portion of the umbilical vein is used, the area is calculated directly26, 28, 29 or from the vessel diameter21, 25, 27 (CSA = π × (diameter/2) 2 ).…”
Section: Accuracymentioning
confidence: 99%
See 1 more Smart Citation
“…The diameter of fetal basilar artery is smaller than the diameter of middle cerebral artery and only a small segment of basilar artery is visualized for waveform acquisition. Since estimates of velocity are derived from the phase shifts or time delays between echoes from the same sample volume during subsequent pulses, the smaller sampling area of the cross‐sectional vessel may result in lower values for flow velocities . The axis of the basilar artery in sagittal view is less favorable than axis of the middle cerebral artery in axial view.…”
Section: Discussionmentioning
confidence: 99%
“…The axis of the basilar artery in sagittal view is less favorable than axis of the middle cerebral artery in axial view. Therefore, manual positioning of probe is technically more difficult to achieve insonation angles of less than 30° . The internal carotid artery and internal jugular vein can be seen in the same plane and require differentiation using anatomical landmarks and waveform analysis.…”
Section: Discussionmentioning
confidence: 99%